2014
DOI: 10.1155/2014/109310
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Size Distribution Models for the Conversion of Chinese Data to FAO/USDA System

Abstract: We investigated eleven particle-size distribution (PSD) models to determine the appropriate models for describing the PSDs of 16349 Chinese soil samples. These data are based on three soil texture classification schemes, including one ISSS (International Society of Soil Science) scheme with four data points and two Katschinski's schemes with five and six data points, respectively. The adjusted coefficient of determination r 2, Akaike's information criterion (AIC), and geometric mean error ratio (GMER) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…In terms of their AIC, the Fred-3p, MLG, Wei and Fred-4p models ranked first to fourth. This result differs from that of Shangguan et al (2014), who found that AD and Wei had the lowest mean AIC values and hence were considered the best PSD models among eleven models that they compared. Considering the average AIC values of all of the soils they studied, Botula et al (2013) suggested that the number of fitting parameters does not always explain the differences in the quality of the fittings.…”
Section: Comparison Of the Fitting Ability Of The Psd Modelscontrasting
confidence: 97%
See 1 more Smart Citation
“…In terms of their AIC, the Fred-3p, MLG, Wei and Fred-4p models ranked first to fourth. This result differs from that of Shangguan et al (2014), who found that AD and Wei had the lowest mean AIC values and hence were considered the best PSD models among eleven models that they compared. Considering the average AIC values of all of the soils they studied, Botula et al (2013) suggested that the number of fitting parameters does not always explain the differences in the quality of the fittings.…”
Section: Comparison Of the Fitting Ability Of The Psd Modelscontrasting
confidence: 97%
“…These and several other efficiency criteria are partly in agreement with published results. For example, in a study evaluating the accuracy of 11 PSD models for the conversion of Chinese data to the FAO/USDA System, Shangguan et al (2014) reported much better performance of the AD, Fred-4p, MLG, and Wei models compared to the other models. Botula et al (2013), Zhao et al, (2011) and Hwang (2004) found the fractal models as well as the Exp and L-E models to be less accurate in their study.…”
Section: Comparison Of the Fitting Ability Of The Psd Modelsmentioning
confidence: 99%
“…The PSD prediction has been used for comparing and converting texture measurements from diverse PSC systems [2,21,27]. For instance, in the Second National Soil Surveys of China, soil textures were measured by ISSS (1929) and Katschinski (1957) PSC systems, in which the conversion from ISSS and Katschinski's to the widely used USDA (1993) PSC system [48,49]. In this study, PSD characteristics which are described by fractal method were investigated because of its simplicity and effectiveness to compare the different PSC systems.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in Section 1, there are no published works evaluating procedures to estimate the VFS fraction of fine earth of soils on the basis of the broad particle‐size classes, neither are there any antecedents for the statistical analysis of texture data drawn from several hundreds of thousands of soil samples. In quantitative terms, the most notable studies to date are Nemes, Wösten, Lilly, and Oude Voshaar (), drawing on 14,584 samples, and Shangguan, Dai, García‐Gutiérrez, and Yuan (), with 16,349 samples, both aimed at evaluating the performance of several procedures and models for describing cumulative particle‐size distributions; the work of Auerswald et al (), with 19,055 samples, along with Panagos et al (), 19,969 samples, both focusing on calculating the K ‐factor; that of Levi (), which included 75,736 samples and tested pedotransfer functions; and that of Padarian, Minasny, and McBratney (), with 160,904 samples, aiming the conversion from Australian to USDA soil particle‐size classification system.…”
Section: Discussionmentioning
confidence: 99%